Goat value chains as platforms to improve income and food security: The case of imGoats in Inhassaro District, Mozambique - Swaans, Cornelis P.M.; Boogaard, Birgit K.; Salazar, Y.A.; Hendrickx, Saskia C.J. (2013)
Innovation platforms are increasingly used as spaces for interaction between actors in value chains to overcome barriers to development. It involves continuous learning and capacity building – both in terms of innovation capacity and specific technical or organizational capacities. Despite the increased use of Innovation Platforms in the context of value chains, there are several questions regarding their practical implementation. This paper aims to gain some insight in their formation and management by sharing experiences from an Innovation Platform for a goat value chain in Inhassoro District, Mozambique. Since the first meeting in May 2011, some of the main lessons include: an Innovation Platform can provide an important mechanism for communication and information exchange to enhance collective action; however, its establishment takes time and needs a lot of facilitation by the project team in the initial stages to ensure proper functioning; moreover, the design and implementation needs to be adapted and negotiated with intended beneficiaries to accommodate seasonality aspects of goat production and marketing, as well as local physical, social and cultural conditions, such as travel distance and literacy rates, gender inequality, and the role goats play in people’s livelihoods.